Genome‐Wide Screening for Lectin Motifs in Arabidopsis thaliana. Issue 2 (1st July 2017) - Eggermont, Lore; Verstraeten, Bruno; Van Damme, Els J.M.
Abstract : For more than three decades, Arabidopsis thaliana served as a model for plant biology research. At present only a few protein families have been studied in detail in Arabidopsis . This study focused on all sequences with lectin motifs in the genome of Arabidopsis . Based on amino acid sequence similarity (BLASTp searches), 217 putative lectin genes were retrieved belonging to 9 out of 12 different lectin families. The domain organization and genomic distribution for each lectin family were analyzed. Domain architecture analysis revealed that most of these lectin gene sequences are linked to other domains, often belonging to protein families with catalytic activity. Many protein domains identified are known to play a role in stress signaling and defense, suggesting a major contribution of the putative lectins in development and plant defense. This genome‐wide screen for different lectin motifs will help to unravel the functional characteristics of lectins. In addition, phylogenetic trees and WebLogos were created and showed that most lectin sequences that share the same domain architecture evolved together. Furthermore, the amino acids responsible for carbohydrate binding are largely conserved. Our results provide information about the evolutionary relationships and functional divergence of the lectin motifs in A. thaliana .